Systematic review of genetic association studies involving histologically confirmed non-alcoholic fatty liver disease. Issue 1 (31st December 2015) - Wood, Kayleigh L; Miller, Michael H; Dillon, John F
Abstract : Non-alcoholic fatty liver disease has an increasing prevalence in Western countries, affecting up to 20% of the population. Objective: The aim of this project was to systematically review and summarise the genetic association studies that investigate possible genetic influences that confer susceptibility to non-alcoholic fatty liver disease and non-alcoholic steatohepatitis. Design: The MEDLINE and SCOPUS databases were searched to identify candidate gene studies on histologically diagnosed non-alcoholic fatty liver disease. Results: A total of 85 articles have been summarised and categorised on the basis of the general pathway each candidate gene is involved in, including lipid metabolism, lipoprotein processing, cholesterol synthesis, glucose homoeostasis, inflammatory response, protection against oxidative stress and whole body metabolism. Conclusions: The main findings demonstrate a small but consistent association of PNPLA3 with non-alcoholic fatty liver disease and non-alcoholic steatohepatitis. Genetic association studies have investigated general disease susceptibility, histological characteristics, severity and progression. However, further study is required to better elucidate the genetic factors influencing fatty liver disease.